Analysis of the Effect of Spatial Planning, Population Density, and Geographic Location on Income Inequality in Indonesia - Haryono, Haryono (Westscience Press, 2025)
This paper analyzes the impact of spatial planning, population density, and geographic location on income inequality in Indonesia, using a normative juridical approach. The study examines the legal frameworks and policies related to spatial planning, population management, and regional development, and how these contribute to or mitigate income disparities across the country. The findings indicate that while Indonesia has established various legal measures, such as the National Spatial Planning Act and Regional Autonomy Law, significant gaps in implementation persist, particularly in balancing urban and rural development. The study suggests that decentralization has led to uneven policy enforcement, with regions in strategic locations experiencing greater economic opportunities compared to remote and isolated areas. Furthermore, legal frameworks often fail to address regional disparities effectively due to insufficient coordination and enforcement. The paper concludes that targeted interventions, stronger enforcement mechanisms, and greater alignment between central and local government policies are crucial for reducing income inequality in Indonesia.